Women, power of collectivity and magical realism in Allende and Kurniawan’s novels: an answer to patriarchal subjectivity - Jamil, Reeti (Brac University, 2021)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.